THE ANALYSIS OF HABITUAL BUYING BEHAVIOUR - Viajeng Purnama Putri (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
This study is to test the effect of information and brand liking support for habitual buying behavior. This research sample of 100 respondents, taken based on Purposive Sampling .The data analysis uses PLS software. This path analysis technique will be used in testing the amount of contribution shown by the path coefficient on each path diagram of the causal relationship between variables X1, X2, on Y. Information support have a positive and significant effect on habitual buying behaviour Brand liking negative effect on habitual buying behavior and information is able to mediate the effect between brand liking on habitual buying behaviour. information and brand liking had positively and significantly influenced the consumer’ responses to habitual buying behavior. The findings of this study contribute to the theory of habitual buying behaviour, namely information and important factors in realizing habitul buying behaviour.